ANALISIS EKUITAS MEREK - Hasan, Ali (Sekolah Tinggi Pariwisata AMPTA, 2010)
Brand equity continues to be one of the critical areas for marketing. This research xxplores some of the consequences attributes may have on brand equity such as the bias on consumer preference. For comparative purposes, this research is conducted on the high involvement using on the four soft drinks brands. This research being measured impact to attributess preferences and actual choice frequence for brand attributes to brand equity. Attributes are examined from a tangible and intangible perspective and both are found to be important contributors to brand equity and brand choice. Keywords: brand equity, consumer preferences, brand attributes.